Development of Creative Thinking Instruments On The Material of Changes In The Form of Objects In Elementary Schools - Arum Dewi Rinjani; Cindy Putri Ranny Azhari; Diana Madya Ratri; Eal Ednov Athallah; M. Anas Thohir (Universitas Nusantara PGRI Kediri, 2026)
This study aims to develop an assessment instrument for creative thinking skills on the material of changes in the state of matter for elementary school students. The study used a research and development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The instrument was compiled based on four indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. In the initial stage, 21 items were developed which were then validated by four validators using Aiken's V and tested for inter-rater reliability using the Intraclass Correlation Coefficient (ICC). The results of content validity showed that 10 items met the valid criteria with an Aiken's V value ≥ 0.92. The inter-rater reliability test showed that the ICC value for each indicator was in the reliable to very reliable category, with a value range between 0.846 and 0.901, which indicated good consistency in inter-rater assessment. The selected instrument was then empirically tested on 27 elementary school students. The results of the empirical validity test using Pearson Product Moment correlation showed that 9 out of 10 questions were declared valid with a rT value of > 0.381. Furthermore, the empirical reliability test using Cronbach's Alpha showed a reliability value in the sufficient category, with a coefficient ranging from 0.427 to 0.570. Based on these results, the creative thinking instrument developed was declared suitable for use as an evaluation tool for students' creative thinking abilities in science learning on the material of changes in the state of objects in elementary schools.